(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the quality of life (QoL) of patients with chronic venous insufficiency (CVI) using the CIVIQ-20 questionnaire. Methods: This cross-sectional study was conducted from September 2022 to June 2024 at the University Medical Center Ho Chi Minh City. A total of 201 patients diagnosed with CVI and indicated for endovenous laser therapy were included. The CIVIQ-20 questionnaire was used to assess the QoL, focusing on four dimensions: Pain, physical, psychological, and social. Results: The mean CIVIQ-20 score was 57.4 ± 8.2, indicating a moderate level of QoL among patients. The social dimension scored the lowest (mean: 8), suggesting that social interactions and activities were the most negatively affected by CVI. Comparatively, patients in this study had a better QoL than those in previous studies conducted in Vietnam, but their QoL was lower than those in studies from other regions. Conclusion: CVI significantly impacts patients’ QoL, particularly in the social domain. Interventions aimed at improving social functioning should be prioritized to enhance the overall QoL in this patient population.